2020
DOI: 10.3390/app10051877
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expandable Retainer for Endoscopic Visualization in the External Auditory Canal: Proof of Concept in Human Cadavers

Abstract: This study was conducted to investigate the efficacy of a self-expandable retainer (SER) for endoscopic visualization of the external auditory canal (EAC). Tympanomeatal flap (TMF) elevation was performed in six cadaveric heads. Two different types of SER were placed. The procedural feasibility was assessed by endoscopic images. Technical success rate, procedure time, endoscopy lens cleaning, and presence of mucosal injuries were analyzed. TMF elevation and SER placement were successful in all specimens and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Surgical instruments that provide adequate control of bleeding, perhaps, for example, with cauterization ability added to suction–dissection, might obviate the need for infiltration. Coupled with an alternative strategy for removing hairs from the field 20 and avoidance of ear packing, 21 around 5-10 minutes could be saved without adversely affecting outcome. Independently from this study, we informally evaluated a commercially available 1-handed sterilizable ear hair trimmer, but found that the hairs were not trimmed sufficiently short and the time saved was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical instruments that provide adequate control of bleeding, perhaps, for example, with cauterization ability added to suction–dissection, might obviate the need for infiltration. Coupled with an alternative strategy for removing hairs from the field 20 and avoidance of ear packing, 21 around 5-10 minutes could be saved without adversely affecting outcome. Independently from this study, we informally evaluated a commercially available 1-handed sterilizable ear hair trimmer, but found that the hairs were not trimmed sufficiently short and the time saved was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical studies show optimization potential for stent development. A self-expandable structure is described in [37]. The complexshaped stent is developed to reduce endoscopic lens cleaning during internal ear visualization.…”
Section: Introductionmentioning
confidence: 99%
“…Other interesting topics of the special materials used in medical field cover the following: Surface Analysis of 3D (SLM) Co-Cr-W Dental Metallic Materials [5], Laser Induced Method to Produce Curcuminoid-Silanol Thin Films for Transdermal Patches Using Irradiation of Turmeric Target [6], Corrosion-Resistance Analysis of HA Layer Deposited through Electrophoresis on Ti4Al4Zr Metallic Substrate [7], Magnetic Abrasive Finishing of Beta-Titanium Wire Using Multiple Transfer Movement Method [8], Effect of Alkyl Structure (Straight Chain/Branched Chain/Unsaturation) of C18 Fatty Acid Sodium Soap on Skin Barrier Function [9] or Self-Expandable Retainer for Endoscopic Visualization in the External Auditory Canal: Proof of Concept in Human Cadavers [10].…”
mentioning
confidence: 99%